Economy and environment program for Southeast Asia - Camille Bann (EEPSEA, 1998)
The main components of this Manual are: an introduction to the values of, and threats to, mangrove ecosystems (Chapter 1); a theoretical introduction to valuation of the environment (Chapter 2); a methodology for the economic assessment of mangrove management options (Chapter 3-9); a qualitative discussion of the possible impacts associated with common development options for mangrove ecosystems (Chapter 10); and, two case-study examples from Asia (Chapter 11)